Ghrelin increases food intake in obese as well as lean subjects - Druce, M R; Wren, A M; Park, A J; Milton, J E; Patterson, M; Frost, G; Ghatei, M A; Small, C; Bloom, S R (International Journal of Obesity, 2005)
OBJECTIVE: To investigate whether effects on food intake are seen in obese subjects receiving exogenous administration of ghrelin. DESIGN: Randomised, double-blind, placebo-controlled study of intravenous ghrelin at doses 1 pmol/kg/min and 5 pmol/kg/min. SUBJECTS: In all, 12 healthy lean subjects (mean body mass index (BMI) 20.5±0.17 kg/m 2 ) and 12 healthy overweight and obese subjects (mean BMI 31.9±1.02 kg/m 2 ). MEASUREMENTS: Food intake, appetite and palatability of food, ghrelin and other obesity-related hormones, growth hormone. RESULTS: Low-dose infusion of ghrelin increased ad libitum energy intake at a buffet meal in the obese group only (mean increase 36.6±9.4%, P <0.01.) High-dose ghrelin infusion increased energy intake in both groups (mean increase 20.1±10.6% in the lean and 70.1±15.5% in the obese, P <0.01 in both cases.) Ghrelin infusion increased palatability of food in the obese group. CONCLUSION: Ghrelin increases food intake in obese as well as lean subjects. Obese people are sensitive to the appetite-stimulating effects of ghrelin and inhibition of circulating ghrelin may be a useful therapeutic target in the treatment of obesity.